EVALUATION OF THE IMPLEMENTATION OF THE JOB CREATION LAW ON LABOR ABSORPTION IN INDONESIA (PERIOD 2020–2025) - Sandra Dewi; Pujy Yonesha; Kiki Razroma Yantika; Riski Murdani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to evaluate the implementation of Law Number 11 of 2020 concerning Job Creation on the absorption of labor in Indonesia during the 2020–2025 period. The birth of the Job Creation Law is expected to be able to accelerate investment and expand employment, especially after the COVID-19 pandemic which has reduced the participation rate of the national labor force. However, the effectiveness of this policy still raises debate, both in terms of the substance of the regulation and its impact on the welfare of workers. This study uses a literature review method by examining secondary data sourced from the Central Statistics Agency (BPS), the Ministry of Manpower (Kemnaker), the Ministry of National Development Planning/Bappenas, as well as the results of previous research published in the 2020–2025 period. The analysis was carried out descriptively by comparing trends in the labor force participation rate (TPAK), open unemployment rate (TPT), and absorption of formal-informal sector labor before and after the implementation of the Job Creation Law. The results of the study show that the Job Creation Law has a positive impact on increasing investment and job creation in several labor-intensive sectors, but still faces challenges in protecting workers' rights, skills gaps, and dominance of the informal sector. In the perspective of maqāṣid al-sharīʿah, the implementation of this policy needs to be directed at the fulfillment of the principles of justice and benefit so that job creation also has implications for the quality of work and the welfare of workers.